Enterprise Interoperability II: New Challenges and Approaches - Gonçalves, Ricardo J.; Müller, Jörg P.; Mertins, Kai; Zelm, Martin (SpringerLink Bücher, 2007)
Enterprise Modelling and Interoperability Engineering -- Distributed, Decentralized and Adaptable Interoperability Architecture -- Tools and Methodologies for Enterprise Interoperability -- Semantics and Knowledge Aspects in Enterprise Interoperability -- Model-driven and Service-oriented Integration and Development -- Collaborative Architecture and Formal Interoperability Approaches -- Managing, Measuring and Validating Interoperability -- Cross-sector Interoperability Solutions -- Applications, Case Studies, Best Practice and Standards.